2008
DOI: 10.1063/1.3033226
|View full text |Cite
|
Sign up to set email alerts
|

Codoping of boron and phosphorus in silicon nanowires synthesized by laser ablation

Abstract: Codoping of boron (B) and phosphorus (P) atoms was performed during the synthesis of silicon nanowires (SiNWs) by laser ablation. The observation of a local vibrational mode of B clearly showed B doping in codoped SiNWs, while Fano broadening due to heavy B doping disappeared, indicating compensation by P donors. The electrospin resonance signal of conduction electrons also disappeared due to compensation by B acceptors. These results indicate that codoping of B and P atoms was achieved in SiNWs during laser a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 18 publications
(15 reference statements)
1
27
0
Order By: Relevance
“…Since postgrowth doping of SiNWs, e.g., by ion implantation, is a difficult process, dopant incorporation is commonly performed during growth by introducing dopant precursors, such as diborane and phosphine for p‐ and n‐type doping, respectively. Dopant or surface modification of the electronic properties of SiNWs has been studied by numerous theoretical and experimental investigations 170–172, 188–197…”
Section: Properties Of Silicon Nanowires For Photovoltaic Applicatmentioning
confidence: 99%
“…Since postgrowth doping of SiNWs, e.g., by ion implantation, is a difficult process, dopant incorporation is commonly performed during growth by introducing dopant precursors, such as diborane and phosphine for p‐ and n‐type doping, respectively. Dopant or surface modification of the electronic properties of SiNWs has been studied by numerous theoretical and experimental investigations 170–172, 188–197…”
Section: Properties Of Silicon Nanowires For Photovoltaic Applicatmentioning
confidence: 99%
“…Numerous works 2,[6][7][8][9] have shown that the single or simultaneous addition of group III-V impurities-like B or P-in a pure Si nanomaterial modifies its electronic structure, enhancing charge carriers concentration and electrical mobility. In particular, in the last years, codoped Si nanocrystals (NCs) and nanowires (NWs) 6,7,[10][11][12][13][14] have been the subject of intense theoretical and experimental studies, which pave the way to very intriguing and exciting technological applications in the field of optoelectronics, high performance nanoelectronics, thermoelectrics, and photovoltaics. For example, Fujii et al 6 have demonstrated that the simultaneous addition of B and P impurities in Si NCs leads to an improvement of the photoluminescence efficiency.…”
mentioning
confidence: 99%
“…Regarding the doping, experiments have shown that Si-NWs can be doped either p-or n-type 13,14 and even codoped, 15 with the possibility of basic functional device applications such as solar cells and nanoelectronic power sources. 16 The main theoretical effort has been dedicated, up to now, to the influence of doping on the electronic and transport properties of Si-NWs, [17][18][19][20][21][22] while an analysis of the dependence of the optical features, is still missing.…”
mentioning
confidence: 99%